Iot Based Patient Health Condition Monitoring - Kaveya.S, Natarajan.S, Sudhersun.S, Santhosh.D, Venkatesh.R (International Journal of Modern Agriculture, 2020)
A few days now IOT plays a major in medical field. Most of the Smart city related projects were deals with smart homes, intelligent transportations, and patient monitoring system under the single concept called IOT. The main objective of this paper is to design and implement of real- time patient health monitoring alarm, especially in the case of patients suffering from sleep during their normal life. In this paper, advanced techniques and services, such as EDM, DS, and NS at the edge of the network were used for monitoring.